Sintesis Oksida Terner Mg-Nb-O dengan Metoda Sol Gel - Kandake, Yonathan
Ternary oxide consists of two metal cations and oxygen. Mg3Nb6O11 ternary oxide phase can be developed as a catalyst in the hydrogen storage material, while MgNb2O6 and Mg4Nb2O9 phase have been developed as a microwave dielectric material. Sol-gel method was used to synthesize the ternary oxide Mg-Nb-O that began with the formation of complex[Mg3(ndc)3(dmf)2(CH3OH)(H2O)](dmf). Complex formation was done by mixing 2 mmol Mg (NO3) 2.6H2O and 1.4 mmol of 2,6-naftalendicarbocylic acid in 40 mL of solvent DMF and CH3OH (50:50). Mixture was heated in an autoclave for 24 hours at a temperature of 110oC. Approximately 0.2 g NbCl5 was added to the resulting complexes then calcinated at 200, 350, 500, 700 and 1000oC. Complex compounds [Mg3(ndc)3(dmf)2(CH3OH)(H2O)](dmf) were characterized using infrared spectroscopy (FTIR) and X-Ray Powder Diffraction (XRD). Phase change was observed in the XRD diffractogram for calcination at 500oC. Ternary oxide which identified in calcination temprature of 500oC were MgNb2O6 (16.05% w/w), Mg3Nb6O11 (52.22% w/w) and Mg4Nb2O9 (10.35% w/w), while the rest is Nb2O5 (6.37% w/w ), MgO (14.98% w / w). Calcination at 700o C causing all of depleted MgO reacts , resulting MgNb2O6 (50.37% w/w), Mg3Nb6O11 (14.75% w/w) and Nb2O5 (34.88% w/w). Further calcination at a temperature of 1000oC only produce MgNb2O6 (84.95% w/w) and Mg4Nb2O9 (15.05% w/w). It can be concluded that Mg3Nb6O11 ternary oxide formed at calcination temperatures around 500o C, whereas for the ternary oxide MgNb2O6 and Mg4Nb2O9 optimally formed at calcination temperatures above 700oC.